Biofilm and Pathogenesis-Related Proteins in the Foodborne P. fluorescens ITEM 17298 With Distinctive Phenotypes During Cold Storage - Quintieri, Laura; Fanelli, Francesca; Zühlke, Daniela; Caputo, Leonardo; Logrieco, Antonio Francesco; Albrecht, Dirk; Riedel, Katharina (Frontiers in Microbiology, 2020)
In food chain, Pseudomonas spp. cause spoilage by reducing shelf life of fresh products, especially during cold storage, with a high economic burden for industries. However, recent studies have shed new light on health risks occurring when they colonize immunocompromised patient tissues. Likewise to P. aeruginosa, they exhibit antibiotic resistance and biofilm formation, responsible for their spread and persistence in the environment. Biofilm formation might be induced by environmental stresses, such as temperature fluctuations causing physiological and metabolic changes exacerbating food spoilage (by protease and pigment synthesis), and the production of adhesion molecules, chemotactic or underestimated virulence factors. In order to provide a new insight into phenotypic biodiversity of Pseudomonas spoilers isolated from cold stored cheese, in this work 19 Pseudomonas spp. were investigated for biofilm, pigments, exopolysaccharide production and motility at low temperature. Only 9 strains showed these phenotypic traits and the blue pigmenting cheese strain P. fluorescens ITEM 17298 was the most distinctive. In addition, this strain decreased the survival probability of infected Galleria mellonella larvae, showing, for the first time, a pathogenic potential. Genomic and proteomic analyses performed on the ITEM 17298 planktonic cells treated or not with lactoferrin derived antibiofilm peptides allowed to reveal specific biofilm related-pathways as well as proteins involved in pathogenesis. Indeed, several genes were found related to signaling system by cGMP-dependent protein kinases, cellulose, rhamnolipid and alginate synthesis, antibiotic resistance, adhesion and virulence factors. The proteome of the untreated ITEM 17298, growing at low temperature, showed that most of the proteins associated with biofilm regulation, pigmentation motility, antibiotic resistance, pathogenecity were repressed or decreased their levels in comparison to that of the untreated cultures. Thus, the results of this work shed a light on the complex pathways network allowing psychrotrophic pseudomonads to adapt themselves to food-refrigerated conditions and enhance their spoilage. In addition, the discovery of virulence factors and antibiotic resistance determinants raises some questions about the need to deeper investigate these underestimated bacteria in order to increase awareness and provide input to update legislation on their detection limits in foods.